Using Thermal Springs to Quantify Deep Groundwater Flow and Its Thermal Footprint in the Alps and a Comparison With North American Orogens - Luijendijk, Elco; Winter, Theis; Köhler, Saskia; Ferguson, Grant; von Hagke, Christoph; Scibek, Jacek (Geophysical Research Letters, 2020)
The extent of deep groundwater flow in mountain belts and its thermal effects are uncertain. Here, we use a new database of discharge, temperature, and composition of thermal springs in the Alps to estimate the extent of deep groundwater flow and its contribution to the groundwater and heat budget. The results indicate that thermal springs are fed exclusively by meteoric water and make up 0.1% of the total groundwater budget. Spring water circulates on average to a depth of at least 2 km. The net heat extracted from the subsurface equals 1% of the background heat flow, which equals an average thermal footprint of 7 km2. Cooling by downward flow and heating by upward flow are three and two times higher than the net heat flow, respectively. Comparison with North American orogens shows that hydrothermal activity is higher in areas with high relief or areas under extension.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Alps; groundwater; heat flow; thermal springs